2016
DOI: 10.1159/000449007
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Concepts in Posterior Subthalamic Area Deep Brain Stimulation for Treatment of Tremor: Surgical Neuroanatomy and Practical Considerations

Abstract: Background: Although thalamic deep brain stimulation (DBS) has been established as an effective therapy for refractory tremor in Parkinson's disease and essential tremor, reports investigating the efficacy of posterior subthalamic area (PSA) DBS for severe, debilitating tremors continue to emerge. However, questions regarding the optimal anatomical target, surgical approach, programming paradigms and effectiveness compared to other targets remain. Objectives: In this report, we aimed to review the current lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…One review hinted at the need for blinded evaluations, 19 and the other review pointed to the need for quality-of-life assessments of patients. 20 It is interesting to note that open-label studies that focused specifically on patients with PD undergoing cZi DBS reported a very positive effect on other symptoms than tremor: Carillo-Ruiz et al 14 evaluated five patients and reported that the UPDRS-III was improved by 65%, with a 90% improvement in tremor, 94% in rigidity and 75% in bradykinesia. In a non-randomised open-label sequential study, Plaha et al 16 compared the effects of DBS in the STN (17 electrodes) and the cZi (27 electrodes) and reported that the best effect was achieved in the cZi with a reduction of contralateral UPDRS-III score by 76%, tremor 93%, rigidity 76% and bradykinesia 65%.…”
Section: Discussionmentioning
confidence: 99%
“…One review hinted at the need for blinded evaluations, 19 and the other review pointed to the need for quality-of-life assessments of patients. 20 It is interesting to note that open-label studies that focused specifically on patients with PD undergoing cZi DBS reported a very positive effect on other symptoms than tremor: Carillo-Ruiz et al 14 evaluated five patients and reported that the UPDRS-III was improved by 65%, with a 90% improvement in tremor, 94% in rigidity and 75% in bradykinesia. In a non-randomised open-label sequential study, Plaha et al 16 compared the effects of DBS in the STN (17 electrodes) and the cZi (27 electrodes) and reported that the best effect was achieved in the cZi with a reduction of contralateral UPDRS-III score by 76%, tremor 93%, rigidity 76% and bradykinesia 65%.…”
Section: Discussionmentioning
confidence: 99%
“…In 7 of these patients, the added dorsal contact was outside of the STN within the region of the rZI [15, 16]. The rZI is located superior to the STN, inferior to the thalamus, lateral to the red nucleus, and medial to the STN.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, although the DRTT passes through posterior subthalamic area (PSA) and caudal zona incerta (cZI), studies of those 2 white-matter targets using conventional imaging were excluded to preserve a focused topic review. The PSA and cZI targets have recently been thoroughly reviewed [49].…”
Section: Methodsmentioning
confidence: 99%